Struktur dan Fungsi Mantra Pengobatan Masyakarat Kanagarian Malai V Suku Kecamatan Batang Gasan Kabupaten Padang Pariaman - Fitri, Yosi Yana; Nasution, Muhammad Ismail (Persona: Kajian Bahasa dan Sastra, 2024)
The purpose of this study was to investigate the structure and function of the treatment mantra of the Nagari Malai V Suku community, Batang Gasan District, Padang Pariaman Regency. This research is categorized as qualitative using descriptive method. The research uses data in the form of texts of community treatment mantras in Nagari Malai V Suku, Batang Gasan District, Padang Pariaman Regency. The instrument of this research is the researcher himself. Data were collected through three stages, namely: (1) literature review, (2) observation and (3) interviews with informants. Data validation was carried out using triangulation techniques. After the data were collected, the data were analyzed with five stages: transcription, transiteration, classification or data analysis, drawing conclusions, and reporting. The results of the research on the structure of the treatment mantra found three parts, namely: opening, content, and closing. The functions of the treatment mantra are divided into five, namely: (a) a system for projection, (b) institutions in cultural institutions, (c) a means to educate, (d) a tool to enforce norms, and (e) a means of treatment. There are three structures in the research, namely the opening, content, and closing structures.